Possibility of preventing peer violence by promoting prosocial value orientation - Jevtić Bisera S.; Đorđević Mariola Z. (University of Kragujevac - Faculty of Pedagogy, Užice, 2018)
Peer violence is a widespread phenomenon in many schools and the dominant problem of today. As peer violence is a significant social problem that can leave irreversible consequences on the development of young people, the imperative of contemporary pedagogy is precisely the prevention of this negative social phenomenon. Our basic assumption is that the encouragement of positive, socially acceptable behavior, or the cultivation of prospective value orientations, forms the basis of all preventive activities and measures in the school directed towards peer violence. In this paper we will analyze the possibility of preventing this negative social phenomenon, precisely by encouraging positive, socially acceptable behavior and developing a prosocial value orientation.